2016
DOI: 10.21037/tau.2016.09.07
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models and prognostic factors for upper tract urothelial carcinoma: a comprehensive review of the literature

Abstract: In the context of customized patient care for upper tract urothelial carcinoma (UTUC), decision-making could be facilitated by risk assessment and prediction tools. The aim of this study was to provide a critical overview of existing predictive models and to review emerging promising prognostic factors for UTUC. A literature search of articles published in English from January 2000 to June 2016 was performed using PubMed. Studies on risk group stratification models and predictive tools in UTUC were selected, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 113 publications
0
17
0
Order By: Relevance
“…The exclusion criteria of a previous UCB will limit the inclusion rate of the REBACARE trial as the majority of patients with urothelial carcinoma of the UUT are known to have had one or more episodes of UCB in their history. However, this was necessary, because it is known that these patients are at much higher risk to develop a subsequent bladder recurrence following surgery for urothelial carcinoma of the UUT [ 11 , 24 , 36 ]. Including these patients will potentially jeopardize the outcome of this trial because it will have an impact on the primary endpoint of this trial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The exclusion criteria of a previous UCB will limit the inclusion rate of the REBACARE trial as the majority of patients with urothelial carcinoma of the UUT are known to have had one or more episodes of UCB in their history. However, this was necessary, because it is known that these patients are at much higher risk to develop a subsequent bladder recurrence following surgery for urothelial carcinoma of the UUT [ 11 , 24 , 36 ]. Including these patients will potentially jeopardize the outcome of this trial because it will have an impact on the primary endpoint of this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed individual patient risk factors for oncologic outcomes [ 5 , 7 , 12 , 24 , 25 ]. Lughezzani et al and Mathieu et al identified tumor stage and grade to be the most significant factors in oncological outcome [ 5 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been clarified that tumors with similar morphological features can have distinct genetic profiles and may belong to different molecular subgroups with different biological behavior ( 1 ). Interestingly, many attempts in these last years have demonstrated the promising predictive value of molecular markers in NMIBC ( 1 , 6 ). For example, a so-called “molecular grade” based on FGFR3 mutation and MIB-1 expression has been proposed and validated, identifying three subgroups at favorable (mutation; normal expression), intermediate (no mutation; normal expression or mutation; high expression) or poor (no mutation; high expression) prognosis ( 5 ).…”
mentioning
confidence: 99%